Multibeam bathymetry processed data (Atlas Hydrosweep DS 3 echo sounder entire dataset) of RV POLARSTERN during cruise PS111, Weddell Sea, Southern Ocean - Boris Dorschel; Simon Dreutter; Jan Erik Arndt; Patricia Slabon; Anne Braakmann-Folgmann (PANGAEA, 2023)
Multibeam data were collected during RV Polarstern cruise PS111 (2018-01-19 to 2018-03-14). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 3 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs, tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional blockmedian grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.